Transforming paddy husk into compost using Bacillus spp. from termite gut to enhance Zea mays L. growth - Freddie Simol, Carlina (2021)
Domestic consumption of rice generated vast amount of paddy husk (PH) as waste. Burning of PH is an approach to instantly eliminate the accumulation of PH but burning can contribute to environmental pollution. Therefore, it is suggested that PH be transformed into a valuable product such as compost that can be used to improved soil fertility and plant productivity. Paddy husk decomposition is difficult due to its high lignin content. Composting of PH with microbes is an alternative method to manage such waste and the termite gut is known for having microbes particularly bacteria that can digest lignin. The objectives of this study were to: (i) screen and identify potential bacteria from termite’s gut as a lignin degrader during PH composting, (ii) determine the nutrient content in PH compost and assess its suitability as a soil amendment, (iii) determine the ability of PH compost to retain and release nutrients into soils, and (iv) determine the effects of PH compost on soil nutrient uptake and maize (Zea mays L.) biomass increment. Composting was carried out for 60 days at Universiti Putra Malaysia Bintulu Sarawak Campus. Three most promising Bacillus spp. were added to polystyrene boxes containing compost mixtures consisting of air-dried PH, chicken feeds, molasses, and leguminous leaves. A control consisting of all raw materials without the inclusion of any additional microbes was also included. Bacillus toyonensis (Bto), B. cereus (Bce), and B. thuringiensis (Bt) was added to T2, T3, and T4 respectively. T5 to T7 were inoculated with a combination of two microbes (Bto + Bce) for T5, (Bce + Bt) for T6, and (Bto + Bt) for T7. T8 was supplied with Bto + Bce + Bt, whereas microbes for T9 were sourced from chicken manure. The decomposition experiment was arranged in a completely randomized design (CRD) with three replications. A soil leaching experiment was conducted for a period of 30 days, whereas the incubation experiment was conducted for a total of 90 days and samples were collected at every 30 days interval to determine the ability of composted PH in retaining nutrients when added to soil. Destructive method was adopted in the sampling of soil for the incubation experiment. The composts were tested in a pot study arranged in a randomized complete block design (RCBD) with three blocks under a controlled environment and maize as a test crop. RCBD was adopted as there were differences in light intensity under the shade house throughout the day due to its surrounding. Maize plants were harvested during tasselling for dry matter determination. Composts with Bacillus spp. gave significant amount of P, Ca, Mg but not total N. Electrical conductivity (EC) was high at 60-day for most treatments and pH was slightly acidic in composts with Bacillus spp. Germination index (GI) in composted PH with Bacillus spp. ranged from 82.51 to 95.83%, indicating non-toxicity. Bacillus spp. showed the ability to degrade wastes with high lignin. Soil pH decreased but total soil P and Mg increased with the incubation period. Plant growth parameters such as height and leaf number significantly increased with composted organic amendments. Organic amendments led to significant increase in plant leaves, stem, and root dry matter yield. Plants treated with compost also showed significantly higher uptake of total N, P, K, Ca, and Mg while composted organic amendments indicated higher pH, total C, P, K, and Mg. The composition of total N, P, and K in composts with Bacillus spp. (T5, T6 and T7) suggested that these composts can be used as soil organic amendments similar to T9 (unidentified microbes from chicken manure) and are recommended for their ability in retaining plant nutrients. These findings indicated that PH composted using microbes extracted from termite gut not only increased the value of composted PH but also increased soil chemical properties, nutrient availability and uptake, and also aided in improving the overall plant growth parameters.